Effect of sucrose concentration of osmotic dehydration pretreatment on drying characteristics and texture of peach chips dried by infrared drying coupled with explosion puffing drying. Issue 15 (18th November 2017) - Lyu, Jian; Yi, Jianyong; Bi, Jinfeng; Chen, Qinqin; Zhou, Linyan; Liu, Xuan
ABSTRACT: Effects of osmotic dehydration (OD) pretreatment on the texture characteristics of peach chips after combination drying were investigated. Peach slices were immersed into 100, 300, and 500 g/L sucrose solution for 4 h, respectively, at room temperature and then predried to a critical moisture content of 0.5 kg water/kg dry matter that was determined by the effective moisture diffusivity ( D eff ) curves under infrared drying at 80°C. The peach chips were then dried using explosion puffing drying (EPD). The sucrose solution with lower concentration (100 g/L) would improve the drying rate (DR) of peach slices during infrared drying. However, sucrose solution with higher concentration (500 g/L) might affect water diffusion, resulting in lower drying rate. The changes of texture characteristics of dehydrated peach were ascribed to sucrose uptake during the impregnation step. The content and constitutes of soluble sugars in peach tissue, which was significantly affected by OD treatment, were also detected in the research. The results indicated that the combined infrared and EPD drying, in which OD with appropriate concentration (300 g/L) was applied as pretreatment, could improve the drying characteristics and texture of peach chips.